PERANCANGAN ALAT TIMBANGAN HEWAN TERNAK MENGGUNAKAN SENSOR FIBER OPTIC DAN SOFTWARE ARDUINO IDE - Rully Syafira Putri; Endang Iriawan; Bambang Widiyatmoko; Elda Rayhana (Institut Sains dan Teknologi Nasional, 2023)
Abstract The type and technique of feeding is the main thing related to the acceleration of livestock development but almost most of the farmers do not pay much attention to the type and quality of feed given to their animals. Therefore, researchers designed the farm animal scales by creating an optical fibre-based sensor and utilizing the Arduino IDE software system for the purpose of making animal farmers aware of the weight information of their animals. The design of the scales has been done in the laboratory of Optoelectronics and Instrumentation, Physics Research Center of Indonesian Institute of Sciences (LIPI) Serpong. The optical fibre sensor system with the received light intensity output was then transmitted by the photodetectors and then Analog to Digital Converter (ADC) process using the Arduino Software. Result of sensor characterization with varying diameter rubber hose with high sensitivity obtained sensor with diameter of 3.1 cm and 2.6 cm. The test results showed that the sensor with a diameter of 3.1 cm was able to withstand pressure of 3.1 kg. F/cm2 or a load equivalent of 905.2 kg. Keywords: Sensors, Optical Fiber, Software Arduino IDE, Livestock